2022
DOI: 10.1186/s40885-022-00197-3
|View full text |Cite
|
Sign up to set email alerts
|

Risks and management of hypertension in cancer patients undergoing targeted therapy: a review

Abstract: Background Rapid progress over the last decade has added numerous agents targeting specific cellular signaling pathways to the treatment armamentarium for advanced cancer. However, many of these agents can cause hypertension resulting in major adverse cardiovascular event. Methods and results A systematic literature search was performed on the databases PubMed and Google Scholar for papers published in English until December 2020. This review summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…This finding could potentially be attributed to the use of HCC-related drugs such as bevacizumab, ramucirumab, sorafenib, and sunitinib, [ 51 ] all of which have been associated with an elevated risk of hypertension in patients with HCC. [ 52 ] Cumulative incidence from CVD increased with age at diagnosis, with multifactorial competing risk analysis showing that older patients were more likely to develop CVD (HR: 3.223 [95% CI: 2.817–3.689]). Interestingly, patients aged 0 to 54 years had the highest SMR for CVD (54.72 [95% CI: 53.51–55.95]), which was similar to the results of Soohwan Kim et al [ 53 ] Younger patients often receive more intense cancer treatments such as radiotherapy, chemotherapy, and surgery, which may cause damage to the cardiovascular system and increase the risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could potentially be attributed to the use of HCC-related drugs such as bevacizumab, ramucirumab, sorafenib, and sunitinib, [ 51 ] all of which have been associated with an elevated risk of hypertension in patients with HCC. [ 52 ] Cumulative incidence from CVD increased with age at diagnosis, with multifactorial competing risk analysis showing that older patients were more likely to develop CVD (HR: 3.223 [95% CI: 2.817–3.689]). Interestingly, patients aged 0 to 54 years had the highest SMR for CVD (54.72 [95% CI: 53.51–55.95]), which was similar to the results of Soohwan Kim et al [ 53 ] Younger patients often receive more intense cancer treatments such as radiotherapy, chemotherapy, and surgery, which may cause damage to the cardiovascular system and increase the risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the involvement of renin-angiotensin and β-adrenergic signaling in blood pressure elevation, cell proliferation, angiogenesis, and tissue invasion highlights the potential importance of inhibiting these pathways for cancer prevention or treatment [ 67 ]. In addition, preclinical studies have demonstrated that some anti-hypertensive drugs have a co-adjuvant effect against chemo-resistant cell lines, inhibit cell growth, and increase chemosensitivity in different cancers [ 63 ].…”
Section: So Why Is the Repurposing Of Anti-diabetic And Anti-hyperten...mentioning
confidence: 99%
“…One may significantly improve their health by following a diet that is low in salt and abundant in fruits, vegetables, and whole grains. Adhering to a consistent schedule of physical activity, limiting alcohol consumption, and cessasion of smoking also have a considerable impact on the prevention of hypertensive disorders [ 131 ]. Various classes of medications used for the treatment of cancer have been associated with the development of new-onset hypertension or exacerbation of previously well-controlled hypertension.…”
Section: Assessment Diagnosis and Management Of Cancer Treatment-indu...mentioning
confidence: 99%
“…In this regard, patients should be informed about the causes of hypertension in cancer patients, including various anti-cancer therapies, and the potential side effects of anti-hypertensive drugs. The caregiver must educate them on which anti-cancer therapies have potential risks for developing malignant hypertension [ 7 , 63 , 131 , 133 , 144 ]. Patients should be educated about lifestyle modifications that can help lower blood pressure, such as weight loss, regular exercise, a healthy diet, and stress reduction.…”
Section: Assessment Diagnosis and Management Of Cancer Treatment-indu...mentioning
confidence: 99%
See 1 more Smart Citation